Do all Indians live in tipis? : questions and answers from the National Museum of the American Indian (Collins, in association with the National Museum of the American Indian, Smithsonian Institution, 2007)
Answers questions about Native Americans, including those related to identity, origins and history, animals and land, language and education, love and marriage, and culture.